Prerequisites for the formation of small and medium business policy in Kazakhstan - Shakeyev, S.S.; Nurmaganbetov, A.S.; Tugina, I.V. (BUKETOV BUSINESS REVIEW, 2017)
The article describes the main stages of small and medium business development, as well as the formation periods of institutional basis of small and medium business in Kazakhstan. These periods of the formation of the institutional basis of small and medium-sized businesses, we divided into 5 main periods (five-year plans), from 1991 to 2016. The article analyzes the main events that occurred during these periods. Small and medium business is very important for the economy of the country, namely for the stability of the economy, preservation and the emergence of jobs, economic growth. Small and medium business includes almost all sectors of the economy, therefore there are many organizations that influence the development of small and medium business, and are also important for its development. Stakeholder analysis, which was used in the work, allowed us to establish such organizations and analyze their impact on the development of small and medium-sized businesses in Kazakhstan. In the work were identified stakeholders of the small and medium business sector of Kazakhstan, the degree of influence and importance of stakeholders in the small and medium business sector of Kazakhstan by conducting interviews and work in focus groups.